Linaburiosides A−D, acylated iridoid glucosides from Linaria buriatica. (March 2020) - Niwa, Kanji; Yi, Ren; Tanaka, Naonobu; Kitaguchi, Shindai; Tsuji, Daisuke; Kim, Sang-Yong; Tsogtbaatar, Ariuntuya; Bunddulam, Perleidulam; Kawazoe, Kazuyoshi; Kojoma, Mareshige; Damdinjav, Davaadagva; Itoh, Kohji; et al.
Abstract: Four previously undescribed acylated iridoid glucosides, linaburiosides A‒D, one undescribed iridoid, 7-deoxyiridolactonic acid, and one known acylated iridoid glucoside, iridolinarin C, were isolated from the aerial parts of a Mongolian traditional herbal medicine, Linaria buriatica . Linaburiosides A‒D had an acyl moiety corresponding to 7-deoxyiridolactonic acid. Detailed spectroscopic analyses of linaburiosides A‒D and 7-deoxyiridolactonic acid led to the assignment of their structures. The absolute configuration of 7-deoxyiridolactonic acid was elucidated by application of the PGME method; those of linaburiosides A‒D were assigned on the basis of chemical conversions, as well as application of the modified Mosher's method. The absolute configuration of iridolinarin C was also elucidated in this study. Anti-inflammatory and antiproliferative activities of isolated compounds and their derivatives were evaluated. Graphical abstract: Image 1 Highlights: Linaria buriatica is a Mongolian traditional herbal medicine. Investigation of the aerial parts of L. buriatica gave linaburiosides A‒D. Their structures were elucidated by spectroscopic analyses and chemical conversions. Linaburiosides A‒D were assigned as hitherto undescribed acylated iridoid glucosides. Anti-inflammatory activity of isolated compounds and their derivatives was evaluated.